Reasons Why Risperidone and Paliperidone Should Not Be Regarded as the Same Drug - Jukić, Marin (Engrami, 2026)
Risperidone and paliperidone are often regarded in clinical practice as closely related, almost interchangeable antipsychotics, primarily because paliperidone, i.e. 9-hydroxy-risperidone, is the main active metabolite of risperidone. This perception of equivalence has led to the widespread use of the concept of the “active moiety,” which refers to the sum of risperidone and 9-hydroxy-risperidone concentrations in blood. Although this concept is useful for therapeutic drug monitoring, it does not imply pharmacological identity between the two molecules. Available data indicate that risperidone and paliperidone differ in their receptor profile, affinity for the dopamine D2 receptor, balance between serotonergic and dopaminergic activity, passage across the blood–brain barrier, and dependence on CYP2D6 metabolism. In addition, the long-acting injectable formulations of risperidone and paliperidone have different pharmacokinetic principles, which further complicates simple dose conversion. This paper discusses the pharmacological and pharmacokinetic reasons why risperidone and paliperidone should not be regarded as the same drugs, but rather as very closely related therapeutic options that may differ in many clinical situations. Special emphasis is placed on the importance of individualizing treatment based on blood drug concentrations, the ratio between risperidone and 9-hydroxy-risperidone, CYP2D6 genetic status, adverse effects, and the choice between oral and long-acting formulations.